Navigating the Geopolitical Landscape: An In-Depth Analysis of Australia's Strategic Position - Charlotte Olivier (GoAcademica Research & Publishing, 2023)
Australia's strategic position in the global geopolitical landscape is a dynamic and multifaceted subject, encompassing factors such as geography, economics, politics, and security. This comprehensive journal article, titled